Dental Caries and Associated Risk Indicators among Married Saudi Women - Bokhari, Syed Akhtar Hussain; Almumtin, Kawthar; Alhashiem, Wala Mohammed; Albandar, Duaa youssef; Alyahya, Zainab Nouh; Alsaad, Ebtihal (European Journal of Dentistry, 2021)
Objective The aim of this study was to evaluate decayed, missing, and filled teeth (DMFT) experience among married females in Saudi Arabia and provide an exploratory data for subsequent primary prevention.Materials and Methods A cross-sectional quantitative study was conducted at a general hospital in Hofuf, Saudi Arabia. All married women attending the general hospital from March 1st to April 15th, 2021 were requested to participate. Data was collected on a validated self-reported questionnaire consisting of sociodemographic factors, medical history, dietary pattern, and DMFT. Descriptive and regression analyses were performed using p ≤0.050.Results Four hundred forty-eight married females with the mean age of 30.81 ± 6.11 years, mean duration of marriage of 9.55 ± 6.58 years, and having average number of children 2.32 ± 1.69 participated in the study. 61.7% mothers had ≥10 years of education. 63.6% were non-working and 56.5% were found with low family income. 66% participants reported of doing exercise less or more often yet 51.7% were ≥overweight. Consumption of energy drinks and dairy products was found significantly associated with increasing number of DMFT. Use of fluoridated toothpaste and dental visits was also found associated with increasing number of dental caries. Increasing age (p = 0.040), increasing number of children, and middle family income were also significantly associated with higher DMFT, respectively (p = 0.002, p = 0.022). In multi-logistic adjusted analysis, only consumption of dairy products, dental visits, and the unsure status of the use of fluoridated toothpaste were significantly associated with DMFT ≥1.Conclusion DMFT status in married Saudi women was associated with participants' dietary habits, oral health-related practices, family income, married years, and number of children.
Keywords: dental caries; decayed, missing, and filled teeth; married women; risk indicators